The Role of Code-Switching in Classroom Interaction: A Case Study of Pharmacy Students at University of Bengkulu - Amirah Zakiah; Elfrida Elfrida; Perti Rosanda (UNIB Press, 2026)
This research focuses on the significance of code switching in communication processes in the classroom between second semester pharmacy students in Bengkulu University. The purpose of this study is to determine the type and function of code-switching and to find out the perception of students regarding code switching in English language learning as an elective subject. This study employed a qualitative research design whereby the data were collected using four observations and interviews with eight respondents from January to February 2026. The data were analyzed based on Poplack's theory of code-switching (1980) to determine types of code-switching, Appel & Muysken theory of code-switching (1980) to determine the functions, and Garrett theory of code-switching (2010) to determine students' perceptions about the code-switching. From the results, all the types of code-switching emerged with the highest frequency in the data, which was the intra-sentential switching at 70 times (50.0%). From the analysis of the function, referential function was the most common at 40 times (21.9%). The students said that code switching enabled them to understand better the lesson, gain confidence, and participate actively in the classroom interaction. This paper therefore finds that code switching is important in English lessons. Hence, teachers are recommended to use flexible language while improving their proficiency in English.